Thermoluminescence responses of the Yb- and Yb-Tb-doped SiO2 optical fibers to 6-MV photons - Sahini, M. H. (Elsevier Ltd., 2014)
Characteristics of the thermoluminescence (TL) responses of Yb- and Yb-Tb-doped optical fibers irradiated with 6. MV photons are reported. The concentration of Yb in the Yb-doped optical fiber was 0.26. mol%; the concentrations of Yb and Tb in the Yb-Tb-doped optical fiber were 0.62 and 0.2. mol%, respectively. The TL dose responses are linear in the dose range 0.5-4. Gy. The radiation sensitivity of the Yb-Tb material is almost two orders of magnitude higher than the sensitivity of the material doped with Yb alone.